2022
DOI: 10.32604/cmes.2022.018507
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Numerical Study of the Effect of the Thickness and the Porosity of the Sand Cushion on the Impact Response Due to the Rockfall

Abstract: The prevention and the reduction of the rockfall are the common measures of the prevention and the reduction of disasters. When the rock-shed resists the impact of the rockfall, the force that acts on the structure consists of the cushion dead load and the impact-induced load, of which the dynamic process of the propagation of the impactinduced load is complex. Therefore, we conducted a numerical study to investigate the impact of the rockfall. Considering the highly discrete characteristic of the sand, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The g s is defined as the surface clearance, that is, the difference between the contact clearance and the reference clearance. The contact force between particles [38,39] can be calculated as:…”
Section: Principles Of Discrete Element Methods (Dem) and The Contact...mentioning
confidence: 99%
“…The g s is defined as the surface clearance, that is, the difference between the contact clearance and the reference clearance. The contact force between particles [38,39] can be calculated as:…”
Section: Principles Of Discrete Element Methods (Dem) and The Contact...mentioning
confidence: 99%
“…The DEM has become a suitable numerical tool for analyzing the impact of rockfalls across various scales (Cundall & Strack, 1979). Many scholars have found DEM to be an effective method for studying the dynamic response of rockfall on the sand cushion (Calvetti et al, 2005;Shen et al, 2021;Yuan et al, 2022;Zhang, Nguyen, et al, 2017). Naito et al (2020) conducted comparative analyses of large-scale rockfall impact DEM simulations and experimental results on different physical parameters of the sand cushion, including thickness, initial relative density, and drop height.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the effect of the particle size on the buffering efficiency of the soil buffer layer can be studied by combining the experiments [10]. The influence of the sand buffer layer thickness and porosity on the buffer performance can also be analyzed by the discrete element numerical method [11]. In these studies, the DEM was found to be an effective method for studying the impact response of sand buffers.…”
Section: Introductionmentioning
confidence: 99%